Safety and efficacy of remimazolam tosilate combined with low-dose fentanyl for procedural sedation in obese patients undergoing gastroscopy: study protocol for a single-centre, double-blind, randomised controlled trial - Xiao Wang; Hao Li; Bin Yang; Lijuan Yan; Zhenyi Chen; Ningning Wu (BMJ Open)
Introduction Obese patients are susceptible to hypoxaemia during procedural sedation. Propofol combined with low-dose opioids is commonly used as a sedation strategy, but it can exacerbate hypoxaemia by causing cardiopulmonary depression and airway obstruction, especially in obese patients. Remimazolam, a novel ultra-short-acting benzodiazepine, has minimal accumulative effects and less cardiorespiratory depression. This study aims to evaluate the safety and efficacy of combining remimazolam tosilate with low-dose fentanyl as an alternative option for procedural sedation in obese patients undergoing gastroscopy.Methods and analysis This randomised controlled trial (RCT) will be conducted in the Endoscopy Centre of the First Affiliated Hospital of Xiamen University, recruiting 174 participants scheduled for painless gastroscopy with a body mass index of 30–39.9 kg×m–2. All patients will be randomly divided into two groups in a 1:1 ratio. The sedation strategy of the intervention group is remimazolam tosilate combined with fentanyl, while the control group is propofol combined with fentanyl. The primary outcome is the incidence of hypoxaemia and the secondary outcomes include the time to ambulation, need for airway manoeuvres and rescue sedation, sleep quality, the incidence of sedation failure, adverse events and the cost of sedatives. All statistical tests will be performed using IBM SPSS V.20.0 statistical software. A p value<0.05 is considered statistically significant.Ethics and dissemination This RCT was reviewed and approved by the Ethics Committee of the First Affiliated Hospital of Xiamen University (Scientific Research Ethics Review 2022, No.093). The results will be published in peer-reviewed journals.Trial registration number ChiCTR2200067076.